Development of Mathematics Teaching Materials Using Didactical Design Research: A Study on Enhancing Pedagogical Content Knowledge in Quadratic Inequalities - Geri Syahril Sidik; Riza Fatimah Zahrah; Mimi Hariyani; Fadhilaturrahmi Fadhilaturrahmi (Papanda Publisher, 2023)
This study presents the development of mathematics instructional materials using the Didactical Design Research (DDR) framework, aiming to enhance the Pedagogical Content Knowledge (PCK) of prospective mathematics teachers in fractional number operations. The research adopted the ADDIE model and encompassed Analysis, Design, Development, Implementation, and Evaluation phases. The evaluation involved expert validators specializing in Didactical Design Research (DDR), subject matter, media, and educators. The resulting Semester Lesson Plan (RPS) assessment scores and teaching materials demonstrated a